Supporting data for identification of biosurfactant-producing bacteria isolated from agro-food industrial effluent - Fulazzaky, Mohamad Ali; Abdullah, Shakila; Salim, Mohd Razman (Elsevier, 2016)
The goal of this study was to identify the biosurfactant-producing bacteria isolated from agro-food industrial effluet. The identification of the potential bacterial strain using a polymerase chain reaction of the 16S rRNA gene analysis was closely related to Serratia marcescens with its recorded strain of SA30 “Fundamentals of mass transfer and kinetics for biosorption of oil and grease from agro-food industrial effluent by Serratia marcescens SA30” (Fulazzaky et al., 2015) [1]; however, many biochemical tests have not been published yet. The biochemical tests of biosurfactant production, haemolytic assay and cell surface hydrophobicity were performed to investigate the beneficial strain of biosurfactant-producing bacteria. Here we do share data collected from the biochemical tests to get a better understanding of the use of Serratia marcescens SA30 to degrade oil, which contributes the technical features of strengthening the biological treatment of oil-contaminated wastewater in tropical environments.